2011
DOI: 10.1210/en.2010-1290
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Increases Astrocytic Vascular Endothelial Growth Factor (VEGF) in Adult Female Rat Hippocampus

Abstract: Vascular endothelial growth factor (VEGF) is critical to angiogenesis and vascular permeability. It is also important in the endocrine system, in which VEGF mediates the vascular effects of estrogens in target tissues such as the uterus, a response attributed to an estrogen response element on the VEGF gene. Here we asked whether 17β-estradiol increases VEGF levels in the brain. We focused on the hippocampus, in which 17β-estradiol and VEGF both have important actions, and used immunocytochemistry to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…However, estrogen treatment before and after ischemia-reperfusion following ovariectomy was seen to markedly restore the impairment to the BBB. In the same vein, previous studies demonstrated that estrogen treatment played a protective role against the hippocampus damage inflicted during global ischemia, and this result lends support to ours (4,12).…”
Section: Discussionsupporting
confidence: 86%
“…However, estrogen treatment before and after ischemia-reperfusion following ovariectomy was seen to markedly restore the impairment to the BBB. In the same vein, previous studies demonstrated that estrogen treatment played a protective role against the hippocampus damage inflicted during global ischemia, and this result lends support to ours (4,12).…”
Section: Discussionsupporting
confidence: 86%
“…2, 3) was labeled with a rhodamine-tagged antibody (Table 1) using methods described previously (Barouk et al 2011; Duffy et al 2013). Briefly, all sections were washed in 0.1 M phosphate buffer (PB) and blocked in 10% donkey serum (Sigma, St. Louis, MO) in 0.25% Triton and 0.005% BSA in 0.1 M PB for 1 h. The sections were then incubated in the goat polyclonal c-fos antibody (Table 1) and either the antibody to GluR2/3, GAD67, PV, NPY, calretinin, or nNOS (Table 1) in 1% donkey serum and 0.25% Triton X-100 in 0.1 M PB for 24 h. Following primary antibody incubation and 3 × 5 min washes in 0.1 M PB, sections were incubated for 2 h in the secondary antibodies (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, BDNF levels fluctuate with the estrous cycle and estrogen administration can increase the expression of BDNF in the PFC and hippocampus 6366 . Dendrite complexity and spine synapse density also fluctuate with the ovarian cycle, and estrogen administration increases spine density in the hippocampus and PFC 6769 .…”
Section: Sex Differences In Susceptibility To Depressionmentioning
confidence: 99%